Prognostic and clinicopathologic significance of SIRT1 expression in hepatocellular carcinoma - Jiang, Hongyuan (Oncotarget, 2016)
The clinical value of SIRT1 in hepatocellular carcinoma (HCC) remains controversial. This meta-analysis was performed to investigate the prognostic and clinicopathological significance of the histone deacetylase SIRT1 in HCC. Pooled hazard ratios (HRs) for survival outcomes and pooled odds ratios (ORs) for clinical parameters associated with SIRT1 were calculated in nine studies using Review Manager. Meta-analysis showed that increased SIRT1 expression is associated with poor overall survival (OS) (HR=1.82, 95% confidence interval (CI): 1.49-2.22, P<0.00001) and disease-free survival (DFS) (HR=1.44, 95%CI: 1.06-1.96, P=0.02) in HCC. Increased expression of SIRT1 is more common in female than male HCC patients (OR=0.47, 95%CI: 0.32-0.70, P=0.0001). The increased SIRT1 expression correlates with hepatitis B virus (HBV) infection (OR=1.63, 95%CI: 1.04-2.57, P=0.03), large tumor size (OR=1.81, 95%CI: 1.05-3.13, P=0.03), high p53 expression (OR=2.71, 95%CI: 1.39-5.29, P=0.003), high levels of alpha-fetoprotein (AFP; cutoff value: 400 ng/ml, OR=1.84, 95%CI: 1.26-2.69, P=0.002), and tumor stage (OR=1.72, 95%CI: 1.27-2.32, P=0.0004). Re-sampling statistics for 5,000,000 samples revealed that increased SIRT1 expression is associated with higher TNM stage (OR=1.70, 95%CI: 1.69-1.70, P<0.00001). These results indicate that SIRT1 is a new biomarker off HCC as well as a potentially effective therapeutic target.